2021
DOI: 10.1007/s40279-021-01615-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Aerobic Exercise on Muscle Strength and Power in Trained Male Individuals: A Systematic Review with Meta-analysis

Abstract: Background Concurrent training can be an effective and time-efficient method to improve both muscle strength and aerobic capacity. A major challenge with concurrent training is how to adequately combine and sequence strength exercise and aerobic exercise to avoid interference effects. This is particularly relevant for athletes. Objective We aimed to examine the acute effects of aerobic exercise on subsequent measures of muscle strength and power in trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 90 publications
1
19
0
Order By: Relevance
“…After warming up, subjects completed a standard incremental loading test to estimate their 1RM strength during the free-weight parallel back-squat exercise. Briefly, the initial external load was set at 20 kg and was progressively increased in 20kg increments when the mean velocity (MV) was greater than 0.75 m•s 21 and increased in 10-kg increments when the MV ranged from 0.75 to 0.60 m•s 21 . The test finished when the MV was less than 0.60 m•s 21 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After warming up, subjects completed a standard incremental loading test to estimate their 1RM strength during the free-weight parallel back-squat exercise. Briefly, the initial external load was set at 20 kg and was progressively increased in 20kg increments when the mean velocity (MV) was greater than 0.75 m•s 21 and increased in 10-kg increments when the MV ranged from 0.75 to 0.60 m•s 21 . The test finished when the MV was less than 0.60 m•s 21 .…”
Section: Methodsmentioning
confidence: 99%
“…A recent review of Vechin et al (37) indicates that long (intensity: ;90-110% of maximal aerobic velocity; duration .60 seconds) and short (intensity: ;110-130% of maximal aerobic velocity; duration ,60 seconds) HIIT protocols performed before RT could compromise muscle strength gains, but very intense HIIT protocols (e.g., sprint interval training [SIT]; intensity: .170% of maximal aerobic velocity; duration: 30-45 seconds) should minimize this interference effect because it presumably induces comparable adaptations to moderate-to heavy-intensity RT. In consensus with the updated model of Vechin et al (37), the meta-analysis from Markov et al (21) demonstrated that higher intensity and longer endurance exercise duration exacerbate acute declines in the strength capacity of the involved muscles. However, to our knowledge, no study has examined the impact of different highintensity running protocols on muscle strength implementing very brief rest intervals (#15 minutes) between the endurance and resistance exercise bouts.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“… 6 Another advantage of adding CT in the training routine is to be more effective in reducing mortality from all causes, than doing only RS or AT alone. 13 This strategy also allows a reduction of the total training time spent in performing the RT and AT in a separate way, 14 without affecting chronic adaptations to exercise. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…Despite these advantages for PF, the training sessions can be very long (i.e., > 60 min) which can be considered a limitation of this strategy [8,9]. However, it allows a reduction in total time spent on performing RT and AT in separate ways [10], without affecting chronic adaptations to training [5,7].…”
Section: Introductionmentioning
confidence: 99%